From the Eloquence of Omar Ibn Al-Khattab (may Allah be Pleased with him): Metaphor as a Model (Islamic Sciences Journal, 2023)
This paper is based on studying the reporting role of the art of metaphor sent in the words of the Commander of the Faithful Omar Ibn Al-Khattab (may Allah be pleased with him), whose words are considered to be among the wonderful prose texts. As they come from a heart illuminated by Allah with his heavenly light, as he addresses generations and not a specific society that is similar in its level of awareness What is said to him, and the research focused on the intellectual, psychological and aesthetic benefit achieved from using the art of the sent metaphor, as it takes us to the early stages of the establishment of the Islamic society, in which the Commander of the Faithful (may God be pleased with him) was adopted. The method of metaphor sent in many places to legislate laws is the most wonderful rule in the history of mankind, and this reflects to us the importance of the transmitted metaphor because it possesses graphic energy and high accuracy in presenting what the speaker wants to convey to addressees of different nationalities in accordance with the conditions of their speech.
Keywords: rhetoric, Omar, speech, metaphor, sender, Amir.